Efficacy and Safety of a Water-Based Head Lice Lotion: A Randomized, Controlled, Investigator-Blinded, Comparative, Bicentric Study - Frank Eertmans; Bart Rossel; Lidia Serrano; Elisabeth Rivera; Els Adriaens (Adis, Springer Healthcare, 2018)
Abstract Introduction Silicones (e.g., dimethicone) are effective and safe alternatives to insecticides for the treatment of head lice. However, silicones are lipophilic substances and do not only leave the hair greasy but they are also difficult to wash out. We have evaluated the efficacy and safety of a potential solution to this problem: an aqueous dispersion of a novel silylated polyol that has the same mode of action as dimethicone (suffocation) without its negative impact on hair characteristics. Methods This was a randomized, controlled, investigator-blinded, bicentric study that was conducted at two locations in the state of Florida (USA) to compare the test product (medical device) to a pyrethrum-based pediculicide that is a first-line, prescription-free treatment against head lice in the USA. The subjects (n = 70) were randomly divided into two groups of 35 persons (test product group and reference product group), with each participant receiving two applications (day 0 and 7) of the product to be tested, according to the instructions for use. Efficacy and safety was evaluated at distinct time points. The primary objective was to establish a cure rate for the test product that was better than 70% at study end (day 10). Esthetic effects of the test product versus dimethicone were evaluated in a blinded, cross-over consumer study (n = 100). Results At study end, the cure rate (corrected for re-infestation) of 88.2% with the test product significantly surpassed the pre-defined target of 70%, and thus the superiority of the test product versus the reference product was confirmed. The number of subjects cured (free of head lice) after the first treatment was remarkably higher with the test product than with the reference product (57.1 vs. 2.9%, respectively). Both products were safe and well tolerated and both showed beneficial esthetical effects. The consumer test demonstrated that the test product had better washing-out properties than dimethicone, as reflected by a significantly lower average rinsing time and number of washings required to restore the visual aspect of the hair, especially in terms of greasiness. Conclusion Aqueous dispersions of silylated polyols are a promising new class of pediculicides that combine high cure rates with optimal user convenience (short treatment period, easy wash-out with positive effect on hair quality). Trial Registration ClinicalTrials.gov identifier, NCT03617926. Funding Oystershell Laboratories.